Carment: Magnesium Cement From Glass Waste As A Solution To The Cement Industry's Carbon Emission Problems - Muhamad Bahrul Ulum; Gracella Audrey Toar; Jihad Akbar Hadrani; Erika Desi Cahyani; Zel Andesra; M Aldi Nugroho (Institut Teknologi Sepuluh Nopember, 2023)
In dealing with carbon emissions generated from the cement industry in general, the author has the idea to use Carment. Carment is a concept of carbon absorbing cement based on magnesium silicate which is derived from silica and is able to reduce carbon emissions from the manufacturing process compared to the manufacture of cement in general. There are several solutions that have existed in overcoming the problem of carbon emissions from the cement industry, such as the Waste Heat Recovery Power Generator (WHRPG), reducing the clinker ratio through blended cement products, and using alternative fuels to replace coal. However, its existence is still quite expensive and has not been able to overcome the problem of carbon emissions resulting from the cement industry. Carment is an innovation in the industrial sector where Carment as a magnesium cement from glass waste can solve the problem of carbon emissions from the calcination process. The availability of glass waste, which has a high availability, contains more than 70% silica and is inexpensive, increases the potential to produce magnesium cement from glass waste in Indonesia.